Library Media Teachers' Perspective on the Student Motivation and Performance Towards the Use of School Resource Centre - Majid, Mayasari Abdul; Shuhidan, Shamila Mohamed; Sani, Mad Khir Johari Abdullah; Dollah, Wan Ab Kadir Ab (UI Scholars Hub, 2020)
This paper presents Library Media Teachers’ (LMT) perspective on student motivation and performance towards the use of School Resource Centre (SRC) for academic purposes. Five LMT from five different schools in Klang Valley, Malaysia were involved in this study. The five schools were selected based on the 5-star rated SRC based on Smart School Qualification Standard (SSQS) rating. The LMT were interviewed individually in order to understand their perspective on the student performance and motivation towards the use of the SRC. In this research, the researchers use the proposed framework to get details on how student performs better and get motivated with the use of the SRC. Findings indicated that, the student perform better and they are highly motivated to study and gain knowledge with the use of SRC. With these findings, there is a hope that school management and Ministry of Education can strengthen the role of SRC in Malaysia.